The Cultural Values Domino Effect: How the Ball Rolls in Influencing University Students' Intentions to Take the Accounting Path - AL Musallami, Ainas Yousuf; Thottoli, Mohammed Muneerali (Universitas Djuanda, 2024)
Students' cultural values can significantly impact their decision to enroll in accounting courses. Some students could be discouraged from studying accounting because of a poor view of the field stemming from cultural expectations. A lack of solid cultural values (Aesthetic, social, symbolic, spiritual, and educational) can negatively affect students aspiring to become accountants. In this context, our study sets out to ascertain how cultural values affect college students' decisions to pursue careers in accounting. With this aim, employing a quantitative technique and a survey questionnaire was appropriate to gather data from Omani undergraduate students. SEM-PLS, version 4.0 software, was used to analyze data. The outcome of our research was mainly the confirmation that cultural values—both symbolic and aesthetic—significantly impact students' decisions to pursue a career in accounting. However, there was no discernible influence of other cultural values (such as social, spiritual, and educational) on the decision to pursue a career in accounting. An accounting career ought to uphold Islamic ideals and beliefs. The capacity to exhibit Islamic beliefs and practices, which students believe is crucial while choosing a career in accounting. The research conclusions of this can help managers in the accounting industry make informed hiring decisions. They can adapt their recruitment efforts to attract talented people by comprehending the variables that affect students' decisions to pursue careers in accounting.